Pendidikan Kesehatan sebagai Upaya Peromotif Pencegahan Penyakit Scbies di Panti Asuhan Harapan Kita Kota Palembang - Intan Kumalasari; Aqnes Salsabila; Aidil Adha Putra A; Fitri Nofiatun Chasanah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Scabies is a contagious skin disease caused by Sarcoptes scabiei infestation, and generally affects children and adolescents, especially those living in crowded and unhygienic environments such as orphanages. This disease is highly contagious through direct contact and the sharing of personal items, such as towels, clothing, and bedding. Therefore, ongoing promotional and preventive efforts are crucial to prevent the spread of scabies in vulnerable communities. This community service activity was carried out at the Harapan Kita Orphanage within the Ariodillah Community Health Center (Puskesmas) working area. The main objective of the activity was to increase children's knowledge, awareness, and skills in preventing scabies transmission. The activity methods used included two-way discussion-based health education, providing real-life examples of personal hygiene, and distributing educational leaflets that are easy for children to understand. The education was conducted interactively by involving participants in questions and answers, handwashing simulations, and education on the importance of washing clothes and maintaining clean bedding. Post-activity observations showed that all participants did not experience active scabies symptoms, and there was an increase in participants' understanding of clean and healthy lifestyles. The children showed high enthusiasm and were able to reflect on the information presented. Overall, this activity proved effective in raising awareness of the importance of personal and environmental hygiene. This counseling model is highly relevant for regular implementation in orphanages or other institutions at high risk of spreading infectious skin diseases, as part of an education-based public health strategy. With the active involvement of the orphanage caregivers, it is hoped that this program can be sustainable and become part of the routine health education for children.